Surface treatment to improve water repellence and compatibility of natural fiber with polymer matrix: Recent advancement. (November 2022) - Mohammed, Mohammed; Rahman, Rozyanty; Mohammed, Aeshah M.; Adam, Tijjani; Betar, Bashir O.; Osman, Azlin F.; Dahham, Omar S.
Abstract: The world is in need of more eco-friendly material, therefore numerous efforts have been made to replace synthetic fibers in fiber-reinforced composites with natural fibers reinforced composite (NFRC), owing to growing environmental consciousness and the depletion of oil supplies. The low cost, low density, abundance, and biodegradability of NFRC, have encouraged several researchers worldwide to study their potential applications in a number of industrial sectors. However, NFRC have several disadvantages, including excessive moisture absorption and subsequent swelling and degradation, low chemical and fire resistance, significant mechanical characteristics dispersion, insufficient interfacial interactions with polymeric or cementitious matrices, etc. Consequently, there is great interest in modifying the surface of NFRC using a variety of methods. This review presents an overview of the NFRC, its characterization, the problems associated with adding NFRC to polymer matrix. The main motive of this article is to review existing research on the surface treatments of NFRC, namely alkali, silane, acetylation, benzoylation, etc., which are all used to reduce moisture absorption and fibers deterioration in order to tackle their obvious disadvantages and effectively employ in a variety of application areas. The effect of these surface treatments on the hydrophilicity, surface chemistry, interface bonding, mechanical characteristics, and thermal performance of NFRC has also been addressed. In addition, we conducted a comprehensive evaluation of the surface treatment of NFRC using nanoparticles (NPs) to increase the hydrophobicity and interfacial bonding between the NFRC and polymer matrix, which might improve the strength and dimensional stability of NFRC. As a result, this review article may make a valuable contribution for researchers interested in coating and treating NFRC to further enhance their surface characteristics. Graphical abstract: Image 1 Highlights: Presents an overview of the NFRC, its characterization, the problems associated with adding NFRC to polymer matrix. Examine the impact of surface treatments on hydrophilicity, surface chemistry, interface bonding, mechanical properties, and thermal performance. Details of each surface treatment method and the benefits and drawbacks of each surface treatment. Using nanoparticles to increase the hydrophobicity and interfacial bonding between the NFRC and polymer matrix.